Śūṭiṅga : 'Ardhasatya' yā citrapaṭācyā citrīkaraṇācī dainandinī - Pānavalakara, Śrī. Dā. (Mumbaī : Mauja Prakāśana Gr̥ha, 1985)
Day to day account of the shooting of Hindi film Ardhasatya.
In Marathi.
Mode of access: Internet.
Keywords: Ardhasatya (Motion picture)